Creative Entrepreneurship Model: The Relationship between Innovation, Competitiveness, and Business Success among the Younger Generation - Fatkhurahman; Idel Waldelmi; Novita (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2026)
This study aims to analyze the Creative Entrepreneurship Model by examining the relationship between creativity, innovation, business competitiveness, and business success among young entrepreneurs in Indonesia. The phenomenon shows that although the young business sector is growing rapidly, its survival rate is still low (BPS, 2024). This condition requires innovative strategies to create sustainable competitive advantages. The approach used is explanatory quantitative with 110 active young entrepreneur respondents. Data were collected through an online questionnaire and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) through SmartPLS 4.0. The results reveal that creativity and innovation have a significant positive effect on business competitiveness and success. Furthermore, business competitiveness was found to mediate the relationship between creativity and innovation and business success, with a path coefficient of 0.469 and a p-value of 0.000. These findings confirm that creativity and innovation are key factors in building superior competitiveness that drives business success. The implication is that young entrepreneurs need to foster a culture of innovation and adaptive strategies to market changes. These results reinforce the Resource-Based View (RBV) theory that long-term competitive advantage depends on the ability to manage unique resources such as creativity and innovation.